Evaluation of tutor performance in problem based learning: rating the skill on students perspective - Yadav, Renu; Mukhopadhyay, Soumitra; Yadav, Subodh Kumar (Journal of Chitwan Medical College, 2020)
Background: The Problem based learning (PBL) was developed at McMaster University School of Medicine in Canada in the 1960s. It has become today’s most accepted method of teaching and learning activities in the field of medicine. A skilled and well-trained tutor plays major role in PBL. Present study is aimed to evaluate tutor performance on student’s perspective based on questionnaire. Methods: This questionnaire-based study was conducted with MBBS I (n=100) and II (n=100) year students of Nobel Medical College and Teaching Hospital. Tutors performance evaluation form was prepared provided with nine question items and the responses were limited to likert scale (1=strongly disagree, 2=disagree, 3=uncertain, 4=agree and 5=strongly agree). Students were instructed to give their opinion and total percentage score along with mean score of every question items were obtained. Then, mean score of each questions were compared between both MBBS batches. Results: Performance of tutors in problem-based learning sessions were analyzed which were obtained as Likert scale score; the percentage score 4 (agree, MBBS I= 52.11 %, MBBS II=53.55 %) followed by 5 (strongly agree, MBBS I=20.77 %, MBBS II= 32.22 %). Mean score obtained for each question items were compared between MBBS I and II year which significantly vary though the majority of scores were 4 (agree) and 5(strongly agree). Conclusions: Satisfactory tutor performance was procured on evaluating the tutor for their skill in PBL as facilitator based on student’s opinion.